News Feature Bicara Karya - Raid Novel; M. Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
“Bicara Karya” as a news feature program created as a new show that can be a source of information and education about the creative industry in the city of Semarang. The program elevates creative industry activities from making, success story, to barriers that occur in a creative industry. Packed with a personal explanation of someone who has expertise in their fields, discussed with a light language but not leaving the essence. In the “Bicara Karya”, The program directors are technically responsible for programming programs both visualizing the manuscript and communicating what they see to the entire production crew (camera person, scriptwriter, voice over, editor, etc.) to realize quality and in accordance with the event's concept and producer's direction. . After going through the pre-production stage, the production process, post production, the work is shown on Cakra Semarang TV every week, starting from 25 April 2017 until 18 July 2017 every Tuesday at 18.00 WIB. Through this work, it is hoped that the public will get educational program to educate and increase the audience information about the creative industry in Semarang and add insight to the viewers. Through the television program